1999
DOI: 10.1002/(sici)1097-4547(19990515)56:4<420::aid-jnr9>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenging compound J 811 inhibits hydrogen peroxide‐induced death of cerebellar granule cells

Abstract: Oxidative stress is considered to be an important pathophysiological condition to promote cell death in a broad variety of disorders, such as cardiovascular and neurodegenerative diseases. Scavestrogens, structurally derived from estradiol, are potent radical scavengers and inhibitors of iron-induced cell damage in vitro. In this study the potential cytoprotective effects of the so-called scavestrogen estra-1,3,5(10),8-tetraene-3,17alpha-diol, J 811, was tested using rat cerebellar granule cells (CGCs) exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(23 reference statements)
1
8
0
1
Order By: Relevance
“…It has been previously reported that oxidative stress induced by H 2 O 2 causes apoptosis of different types of nerve cells, including granule cells (Bhat & Zhang, 1999; Gotz et al ., 1999; Mailly et al ., 1999; Wei et al ., 2000). We have recently demonstrated that PACAP promotes the survival of immature granule cells (Gonzalez et al ., 1997) through inhibition of caspase‐3 activity (Vaudry et al ., 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that oxidative stress induced by H 2 O 2 causes apoptosis of different types of nerve cells, including granule cells (Bhat & Zhang, 1999; Gotz et al ., 1999; Mailly et al ., 1999; Wei et al ., 2000). We have recently demonstrated that PACAP promotes the survival of immature granule cells (Gonzalez et al ., 1997) through inhibition of caspase‐3 activity (Vaudry et al ., 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals and other active compounds have been suggested to be involved in many biological processes, including ageing and various chronic diseases. Oxidative stress originates as the result of an imbalance between the generation of ROS, such as superoxide (O 2 • – ), hydroxy radicals (HO•) and hydrogen peroxide (H 2 O 2 ), and cellular anti‐oxidants 1,19 . These ROS, if not scavenged in a timely fashion, may cause oxidative damage to macromolecules, such as DNA 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Both H 2 O 2 and MeHg cause an increase in intracellular reactive oxygen species and intracellular Ca 2ϩ (30,31). Instead, the toxic effects of colchicine are mainly at the cytoskeletal level and cannot be blocked by antioxidants (15) or Ca 2ϩ channel blockers (12).…”
Section: Discussionmentioning
confidence: 99%
“…On day 7, cell viability was analyzed by evaluating living cell permeability to impermeant DNA dies. Cells then were exposed for 24 h to 25 M H 2 O 2, 1 M MeHg, or 1 M colchicine, stimuli inducing chromatin condensation and appearance of high molecular weight DNA fragments (12)(13)(14)(15)(16). For biochemical analyses on unexposed cells, CGC were collected after 1 week in culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation